Amplitude contrast image enhancement in digital holography for particles analysis - Singh, Vijay Raj (2011)
In-line digital holography is presented for the particles analysis in 3-D. The presence of zero order wave, conjugate image wave, and defocused images degrade the image quality in in-line digital holography. In this paper we utilise the numerical reconstruction process to minimise these effects. We present a new subtraction method of reconstructed wave fields for particles analysis. The effects of zero order term, conjugate image wave and more importantly the particles outside the plane of interest (defocused images) are simultaneously minimized, and thus improve the contrast of reconstructed amplitude images. This method is useful to slice in-line digital holograms to display only in-focus particles at any particular plane. Furthermore all this is accomplished from a single hologram with no additional pre or post processing required.